Electro-optic comb based real time ultra-high sensitivity phase noise measurement system for high frequency microwaves - N. Kuse (Nature Portfolio, 2017)
Abstract Recent progress in ultra low phase noise microwave generation indispensably depends on ultra low phase noise characterization systems. However, achieving high sensitivity currently relies on time consuming averaging via cross correlation, which sometimes even underestimates phase noise because of residual correlations. Moreover, extending high sensitivity phase noise measurements to microwaves beyond 10 GHz is very difficult because of the lack of suitable high frequency microwave components. In this work, we introduce a delayed self-heterodyne method in conjunction with sensitivity enhancement via the use of higher order comb modes from an electro-optic comb for ultra-high sensitivity phase noise measurements. The method obviates the need for any high frequency RF components and has a frequency measurement range limited only by the bandwidth (100 GHz) of current electro-optic modulators. The estimated noise floor is as low as −133 dBc/Hz, −155 dBc/Hz, −170 dBc/Hz and −171 dBc/Hz without cross correlation at 1 kHz, 10 kHz, 100 kHz and 1 MHz Fourier offset frequency for a 10 GHz carrier, respectively. Moreover, since no cross correlation is necessary, RF oscillator phase noise can be directly suppressed via feedback up to 100 kHz frequency offset.